2012
DOI: 10.1186/1471-2202-13-29
|View full text |Cite
|
Sign up to set email alerts
|

Unmyelinated nerve fibers in the human dental pulp express markers for myelinated fibers and show sodium channel accumulations

Abstract: Background The dental pulp is a common source of pain and is used to study peripheral inflammatory pain mechanisms. Results show most fibers are unmyelinated, yet recent findings in experimental animals suggest many pulpal afferents originate from fibers that are myelinated at more proximal locations. Here we use the human dental pulp and confocal microscopy to examine the staining relationships of neurofilament heavy (NFH), a protein commonly expressed in myelinated afferents, with other markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 77 publications
(92 reference statements)
3
28
0
Order By: Relevance
“…Regarding the size of SP+ axons, even if estimations of axons' size is fairly unreliable due to the overlapping between A and C fibres (Bear et al 2007;Ruscheweyh et al 2007), the presence of axons of 0.6 and 5 lm in equine menisci suggest the presence of C and A fibres, respectively. Furthermore, our results are mostly in accord with Henry et al (2012), who reported that Schwann's cell nuclei with a more rounded appearance surrounded A myelinated fibres while elongated nuclei were associated with C unmyelinated fibres. Indeed, we found these two different shapes of nuclei, which correlates with the presence of two types of fibres, with the exception of Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the size of SP+ axons, even if estimations of axons' size is fairly unreliable due to the overlapping between A and C fibres (Bear et al 2007;Ruscheweyh et al 2007), the presence of axons of 0.6 and 5 lm in equine menisci suggest the presence of C and A fibres, respectively. Furthermore, our results are mostly in accord with Henry et al (2012), who reported that Schwann's cell nuclei with a more rounded appearance surrounded A myelinated fibres while elongated nuclei were associated with C unmyelinated fibres. Indeed, we found these two different shapes of nuclei, which correlates with the presence of two types of fibres, with the exception of Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Without myelin, excitable membranes are found in close proximity, allowing for the establishment of ephaptic connections and cross-talk between neurons, which compromises the integrity of a transmitted signal and makes it possible for dispersion and amplification of signals that enter the central nervous system [65]. Additionally, the number of sodium channels increases dramatically and is inserted into the exposed membranes [16,25,62,64,[66][67][68][69][70], resulting in the generation of ectopic discharges. The resulting increase in regional excitability is thought to be associated with the perception of tingling, burning, sharp, and shocking pain [71].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of pulpal fibers by thermal, mechanical or electrical stimuli almost always results in a sensation of pain [42; 49]. Interestingly, the majority of pulpal neurons are, in fact, low threshold mechanosensitive fibers rather than classical nociceptors [24; 29]. Outside of the tooth the axons of these neurons are myelinated, but they become unmyelinated upon entering the tooth, where the fibers branch extensively [9; 23; 26; 63].…”
Section: Introductionmentioning
confidence: 99%